Masters of Mankind: Essays and Lectures - Noam Chomsky (Hamish Hamilton, 2015)
"In this collection of essays from 1969-2013, many in book form for the first time, Noam Chomsky exposes the real nature of state power. With unrelenting logic, he holds the arguments of empire up to critical examination and shatters the myths of those who protect the power and privilege of the few against the interests and needs to the many"-- Provided by publisher.